2016
DOI: 10.1103/physrevlett.117.256102
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Structure of the Oil-Water Interface

Abstract: X-ray reflectivity (XR) and atomistic molecular dynamics (MD) simulations, carried out to determine the structure of the oil-water interface, provide new insight into the simplest liquid-liquid interface. For several oils (hexane, dodecane, and hexadecane) the XR shows very good agreement with a monotonic interface-normal electron density profile (EDP) broadened only by capillary waves. Similar agreement is also found for an EDP including a sub-Å thick electron depletion layer separating the oil and the water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 28 publications
10
30
0
Order By: Relevance
“…Thus, the nearly flat spectral response found in the SSP spectra, and minimal response in PPP polarization combination, indicate the interfacial hexadecane lies relatively parallel to the interface. This is consistent with X-ray reflectivity measurements and molecular dynamics simulations (28). Furthermore, the presence of a minimal CH stretching response for bare hexadecane droplets supports computational work concluding there must exist a rough alkane surface necessary to provide space for a free OD to exist (12).…”
Section: Water Bonding and Hydrophobic Structuring At The Lcne Surfacesupporting
confidence: 85%
“…Thus, the nearly flat spectral response found in the SSP spectra, and minimal response in PPP polarization combination, indicate the interfacial hexadecane lies relatively parallel to the interface. This is consistent with X-ray reflectivity measurements and molecular dynamics simulations (28). Furthermore, the presence of a minimal CH stretching response for bare hexadecane droplets supports computational work concluding there must exist a rough alkane surface necessary to provide space for a free OD to exist (12).…”
Section: Water Bonding and Hydrophobic Structuring At The Lcne Surfacesupporting
confidence: 85%
“…On a molecular level, the mechanism for this trend might lie in the structure of the alkane/water interface. It has been observed that an interfacial electron depletion layer with a thickness δ exists between water and hydrophobic alkane chains by both X-ray reflectivity (XR) measurements 39 41 and atomistic molecular dynamics (MD) simulations 42 , 43 . The few water molecules in the depletion layer (electron density < 40% that of bulk water 44 ) can buckle in the intermolecular space near the ends of alkane molecules (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3b ), and create a template for the formation of an ice nucleus 29 . The alkane chains adjacent to the water molecules preferentially have their longest axis parallel to the water interface with a tilt angle β 39 . This tilt angle increases with m and l , resulting in a more parallel orientation for longer alkanes 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the effect of an external field on fluids is fundamentally important, theoretical treatment of interfaces in a field have received only limited attention with almost no work on capillary waves [9][10][11][12][13]. This is despite the importance of capillary waves in the nanoscale structure of interfaces [14][15][16][17]. A relation between the amplitude of the capillary waves, the field strength, and surface stiffness is lacking and measuring these quantities experimentally is difficult, which makes developing an empirical relation among these quantities a challenge.…”
Section: Introductionmentioning
confidence: 99%